Foreign language teacher preparation in Slovakia and Poland from skills to competences - Kováčiková, Elena; Kic-Drgas, Joanna (Glottodidactica, 2023)
The paper discusses the challenges of foreign language teacher preparation in Slovakia and Poland resulting from observed tendencies such as digitalisation, mobility and specialisation of disciplines. The background for these reflections on the state of teacher training education is the document European Profile for Language Teacher Education – a Frame of Reference (2004) and DigComp 2.2 The Digital Competence Framework for Citizens (2022), which point out the main fields essential for the development of high-quality foreign language teachers in terms of digital, life and entrepreneurial competences. The authors of the paper analyze example curricula at two universities, one in Poland (Adam Mickiewicz University, Poznań) and one in Slovakia (Constantine the Philosopher University in Nitra) to answer the following research questions: how will future foreign language teachers be supported in developing their competences at the tertiary level? How do the current foreign language teacher training curricula at universities in Slovakia and Poland incorporate the need for the development of new competences? The results of the analysis present the discrepancies at both universities in the way the recommendations concerning competence development are incorporated, however they also reveal the weaknesses and strengths of the existing solutions.